The Effects Of Hydrogen-Rich Water Ingestion On The Symptoms Of Eccentric Exercise-Induced Muscle Damage Ros - Abdullah, Ros Amizah (2019)
Post-exercise muscle damage manifests as a decline in the force-generating ability and delayed-onset muscle soreness (DOMS). Until today, there is no single best method to alleviate these conditions. Recently, the beneficial effects of hydrogen-rich water (HRW) have been described in experimental and clinical disease conditions. This prospective research was aimed to evaluate the ability of HRW to reduce the severity of strength decline and DOMS post-exercise in healthy as well as physically active male youths. In a randomized crossover manner, 11 adult males (24 ± 4 years) received 1.7 L·day-1 of either HRW or placebo for 14 days, with a 28-day washout period between the trials.